Problemy w przebiegu pierwszej fazy rozwoju wg koncepcji Erika Eriksona u dziecka niewidomego - GŁADYSZEWSKA-CYLULKO, JOANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Joanna Gładyszewska-Cylulko, Problemy w przebiegu pierwszej fazy rozwoju wg koncepcji Erika Eriksona u dziecka niewidomego [Problems of the first stage of psychosocial development according to Erik Erikson in a blind child]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 139-166. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.08 Erik H. Erikson, the author of the theory of psychosocial development, claimed that during their life from birth to death, every human being experiences eight developmental crises. Every time, at each stage there are two polar opposites, two conflicting values. To overcome the crisis we must find an optimal balance between them. How we resolve the crises affects our integration and relations with others and ourselves. In the article the author concentrates on the first developmental stage, considered by many to be the most important one. Its two opposites are basic trust and basic mistrust, while the basic virtue is hope. Unfortunately, due to the lack of appropriate experiences, improper attitude of other people and various other factors, blind children already at this stage often fail to properly resolve the developmental crisis. In further part of the article the author discusses the causes of the problem and suggests how the disturbances at the first stage of development might be prevented.